The Permeability Alternation of Shale Fractures due to Sc-CO2 Soaking: Implications for Sc-CO2 Fracturing and Deep CO2 Sequestration in Shale Reservoirs - Zhaohui Lu; Yunzhong Jia; Jiankun Zhou; Pei He; Menglai Li; Zhengyang Song; Xin Cai (Advances in Materials Science and Engineering)
The shale fracture permeability is critical in determining gas production and deep CO2 sequestration performance. Moreover, how shale fracture permeability evolves after interactions with supercritical carbon dioxide (Sc-CO2) should be understood to constrain the shale reservoir permeability and evaluate the long-term sealing ability of shale formations. In this research, we conducted soaking experiments with shale fractures and Sc-CO2 at various times and then measured the shale fracture permeability and hydraulic aperture evolution under different stress states. Additionally, we quantify the chemical compositions, pore characteristics, fracture surface roughness alternation through X-ray diffraction, nuclear magnetic resonance, scanning electron microscope, and optical profilometry techniques. Our results indicate that soaking with Sc-CO2 will dramatically increase the shale fracture permeability and aperture due to the calcite and dolomite dissolution. This free-face dissolution process will remove the mineral particles in the fracture surface, resulting in larger pores, peaks, and valleys in the fracture surfaces. This process may last for seven days, and after that, chemical reactions may terminate, and the rock-Sc-CO2 system turns stable. Our results explain how Sc-CO2 alters the shale fracture permeability through the chemical dissolution of specific minerals from a microscale analysis.